Conflict handling behavior : a study on administrative and diplomatic officer - Mohd Zahari, Bin Razali (Universiti Malaysia Sarawak, (UNIMAS), 2002)
The primary objective of this study is to examine the conflict-handling styles "dominance" officers in Malaysia Civil Service - namely Administrative and Diplomatic Officer / Pegawai Tadbir dan Diplomatik (thereafter reffered as PTD)